1991
DOI: 10.1002/jcp.1041470210
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ornithine decarboxylase mRNA by phorbol esters and insulin in normal and C‐kinase‐deficient rat hepatoma cells

Abstract: Tumor-promoting phorbol esters and insulin produce similar effects in Reuber H35 rat hepatoma cell proliferation, including increased ornithine decarboxylase (ODC) enzyme activity, DNA synthesis, and mitogenesis. We investigated ODC mRNA accumulation in cells treated with either insulin or 12-O-tetradecanoyl-phorbol-13-acetate (TPA). Both agents caused rapid accumulation of ODC mRNA: for TPA, it was maximal 3 hr after treatment (4-6-fold greater than control cells) and returned quickly to control levels; for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…The mRNAs of keratin 18 (Krt1-18) and, in line with earlier reports [35][36][37][38], ornithin decarboxylase (Odc1) and actin (Acta1) were downregulated by hyperosmolarity but upregulated by insulin (Table 2B, no. 68, 53 and 47).…”
Section: Osmoregulated Genessupporting
confidence: 77%
“…The mRNAs of keratin 18 (Krt1-18) and, in line with earlier reports [35][36][37][38], ornithin decarboxylase (Odc1) and actin (Acta1) were downregulated by hyperosmolarity but upregulated by insulin (Table 2B, no. 68, 53 and 47).…”
Section: Osmoregulated Genessupporting
confidence: 77%
“…In addition, previous studies suggested that ODC could represent a downstream element of PKC-mediated mitogenic signalling [29][30][31], and might be involved in tumour cell invasion in vitro [32][33][34][35]. These data raised the possibility that ODC also played a role in the abovementioned actions of PKC on the invasiveness of the glioma cell lines.…”
Section: Involvement Of Odc In Pkc-mediated Mt1-mmp Expression Mmp-2mentioning
confidence: 69%
“…Available in vitro data suggest an involvement of mitogen-activated protein kinase/extracellular-signal-regulated kinase 1 (MEK-1) and ODC in the stimulatory effects of PKC on tumour cell proliferation [29][30][31], while ODC and extracellular-signal-regulated kinases 1 and/or 2 (ERK1/2) have been implicated in tumour cell invasion [32][33][34][35][36][37][38]. Therefore, we also asked whether these enzyme systems were involved in the actions of PKC on the invasiveness of the glioma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…HindIII fragment (16) Pups of three or four pregnant rats in each group were used for each datum point. We measured tissue ODC activity in five pups per litter and calculated the mean value.…”
mentioning
confidence: 99%